ANALISIS SEMIOTIKA FEMINISME EKSISTENSIALIS TOKOH â€œJUDYâ€ DALAM FILM ANIMASI ZOOTOPIA BAGI MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS SWADAYA GUNUNG JATI - Kurniasih, Nia; Zulkarnaen, Iskandar; Nurfalah, Farida (Konvergensi, 2023)
This study is entitled "Semiotic Analysis of Existentialist Feminism as the Character "Judy" in the Zootopia Animation Film for Students of the Faculty of Social and Political Sciences, Swadaya University Gunung Jati". The animated film Zootopia produced by Clark Spencer is an animated adventure-comedy genre film produced by Disney in 2016. The film Zootopia tells the story of a rabbit named Judy Hopps who lives in the town of Bunnyburrow. Judy has a dream to go to Zootopia, a city where all animals can coexist harmoniously and Judy has a dream to become a rabbit policeman for the first time in that city. So in this case, the researcher formulates the problem, namely how the meaning of denotation, connotation and myth of existentialist feminism character "Judy" in the animated film Zootopia. The purpose of this study is to find out the meaning of the scenes in the animated film Zootopia by looking at the denotative meanings, connotative meanings and myths related to Simone de Beauvoir's existentialist feminism values â€‹â€‹in the character Judy. The research method used in this study is a qualitative method with Roland Barthes's semiotic analysis. Based on the results of research conducted by the author, it can be concluded that the meaning of denotation in each scene already describes the value of existentialist feminism in the character Judy. Focusing on each scene that depicts Judy's expressions and conversations in determining the path of life she aspires to. Then the connotative meaning, in every scene in the film is related to the value of existentialist feminism, namely how the hidden meaning contained in each scene is like how Judy as an existentialist feminist shows and fights for her existential freedom. Meanwhile, the meaning of the myth that the author finds in every scene in the film is related to the value of existentialist feminism, namely things that are believed by film audiences, for example, as a woman, you must know the purpose of life as well as struggle and maintain your ideals. Through the myth built by the character Judy in the animated film Zootopia, there is a myth that spreads with the term 'Assembling upstream, swimming to the shore' in other words, if you want to be successful, you have to be brave enough to work hard first. Keywords: Existentialist, Feminism, Zootopia, Film.